Goal‐directed EEG activity evoked by discriminative stimuli in reinforcement learning. (6th August 2014) - Luque, David; Morís, Joaquín; Rushby, Jacqueline A.; Le Pelley, Mike E.
Abstract In reinforcement learning (RL), discriminative stimuli (S) allow agents to anticipate the value of a future outcome, and the response that will produce that outcome. We examined this processing by recording EEG locked to S during RL. Incentive value of outcomes and predictive value of S were manipulated, allowing us to discriminate between outcome‐related and response‐related activity. S predicting the correct response differed from nonpredictive S in the P2. S paired with high‐value outcomes differed from those paired with low‐value outcomes in a frontocentral positivity and in the P3b. A slow negativity then distinguished between predictive and nonpredictive S. These results suggest that, first, attention prioritizes detection of informative S. Activation of mental representations of these informative S then retrieves representations of outcomes, which in turn retrieve representations of responses that previously produced those outcomes.